Neonatal Sepsis in Low Birth Weight Infants in Dr. Soetomo General Hospital - Utomo, Martono Tri (Indonesian Journal of Tropical and Infectious Disease, 2010)
Infections of the newborn are a significant cause of mortality. Preterm infant have a high risk sepsis.. The incidence of neonatal  sepsis is 1 to 10 cases per 1000 live births and 1 per 250 live premature births. To describe the characteristics of neonatal sepsis in the low birth weight infant in the neonatal intensive care unit Dr. Soetomo Hospital. Retrospective analysis. The data were collected from the medical record of low birth weight infants who were diagnosed as sepsis in neonatal care unit of Dr. Soetomo Hospital between January 2010 to June 2010 with purposive sampling. Descriptive analysis of risk factor of sepsis and blood culture of the patient was calculated. Chi-square analysis was performed in the laboratorium data. Characteristics sample: male vs female 61% vs 39%, outcome of sepsis in LBW was death 69%, alive 25%, risk of infection: turbid amniotic fluid 21%, asphyxia 33%. Laboratorium data leucopenia and thrombocytopenia (P < 0.05). Blood culture: Klebsiella pnemoniae. The incidence and mortality of neonatal sepsis in LBW infants was still high. Asphyxia, turbid amniotic fluid, leucopenia and thrombocytopenia were associated with sepsis. pneumoniae was the most common organisms in the LBW sepsis infants.